2001
DOI: 10.1021/bi011029y
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Release and Associated Conformational Changes Regulate Function in the COOH-Terminal Src Kinase, Csk

Abstract: The COOH-terminal Src kinase (Csk) regulates a broad array of cellular processes via the specific phosphorylation and downregulation of Src family protein kinases. While Csk has been a topic for steady-state kinetic studies, the individual steps associated with substrate phosphorylation have not been investigated. To understand active-site phenomena, pre-steady-state and transient-state kinetic methods were applied to develop a catalytic pathway for substrate processing. Rapid quench flow techniques show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 45 publications
1
50
1
Order By: Relevance
“…The DFG flip has been suggested to promote ADP release (27), the rate-limiting step in kinase catalysis (42)(43)(44). Intriguingly, our results could be interpreted as hinting at a mechanistic explanation for such a proposed role.…”
Section: Conservation Of the Dfg Motif And Its Role In Kinase Catalysissupporting
confidence: 58%
“…The DFG flip has been suggested to promote ADP release (27), the rate-limiting step in kinase catalysis (42)(43)(44). Intriguingly, our results could be interpreted as hinting at a mechanistic explanation for such a proposed role.…”
Section: Conservation Of the Dfg Motif And Its Role In Kinase Catalysissupporting
confidence: 58%
“…For these studies, we exploited the unique advantages of pre-steady-state kinetic methods for establishing catalytic mechanisms. In the past, we (18,33) and others (23,34) have demonstrated that these methods are well suited for investigating important catalytic features of both simple and multidomain protein kinase systems.…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2) indicate that the phosphoryl transfer step is fast, these results do not provide information as to which product release step (ADP or phospho-Npl3) limits turnover. Although ADP dissociation limits peptide phosphorylation in several protein kinases (19,33,34), it is unclear whether the presence of a real physiological protein substrate could change this rate-limiting step. To address this question, a catalytic trapping protocol originally developed in our laboratory for protein kinase A was employed (19,21).…”
Section: Rate-limiting Step For Npl3 Phosphorylation: Catalytic Trappmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein Purification-A full-length form of human Csk with a C-terminal polyhistidine tag was expressed in Escherichia coli strain BL21(DE3) and purified with a Ni 2ϩ -agarose column according to a previously published procedure (23). A GST form of Csk (GST-Csk) was also expressed in E. coli strain BL21(DE3) and purified as previously described (24). A mutant form of chicken Src lacking the first 82 residues and possessing a lysine-to-methionine substitution at position 295 was coexpressed with GroEL/ES chaperonin proteins in E. coli strain BL21(DE3) and purified using a Ni 2ϩ -agarose column according to a previously published procedure (19).…”
mentioning
confidence: 99%